2015
DOI: 10.1038/ni.3103
|View full text |Cite
|
Sign up to set email alerts
|

IL-37 requires the receptors IL-18Rα and IL-1R8 (SIGIRR) to carry out its multifaceted anti-inflammatory program upon innate signal transduction

Abstract: Interleukin 37 (IL-37) and IL-1R8 (SIGIRR or TIR8) are anti-inflammatory orphan members of the IL-1 ligand family and IL-1 receptor family, respectively. Here we demonstrate formation and function of the endogenous ligand-receptor complex IL-37-IL-1R8-IL-18Rα. The tripartite complex assembled rapidly on the surface of peripheral blood mononuclear cells upon stimulation with lipopolysaccharide. Silencing of IL-1R8 or IL-18Rα impaired the anti-inflammatory activity of IL-37. Whereas mice with transgenic expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
456
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 373 publications
(490 citation statements)
references
References 49 publications
27
456
1
6
Order By: Relevance
“…IL‐37 has been identified as a natural suppressor of innate inflammatory and immune responses 8, 12. Recent studies have indicated that IL‐37 plays a protective role in tumor progression in mouse fibrosarcoma,9 human lung cancer,14, 42 hepatocellular carcinoma,13 breast cancer,43 cervical cancer,44 and renal cell carcinoma 45.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL‐37 has been identified as a natural suppressor of innate inflammatory and immune responses 8, 12. Recent studies have indicated that IL‐37 plays a protective role in tumor progression in mouse fibrosarcoma,9 human lung cancer,14, 42 hepatocellular carcinoma,13 breast cancer,43 cervical cancer,44 and renal cell carcinoma 45.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, entirely distinct with most IL‐1 family members, that are characterized with proinflammatory functions, IL‐37 has emerged as an important inhibitor of the innate immune response. With the accumulated evidence, IL‐37 has been recognized as a typical anti‐inflammatory cytokine related to autoimmune diseases, endotoxemia, inflammatory liver injury, obesity, and cancer 8, 9, 10, 11, 12. Gao et al9 found that the intratumoral injection of IL‐37 inhibited tumor growth and the antitumor activity of IL‐37 was abrogated in mice models.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SIGIRR has long been considered as an orphan receptor with unknown ligand molecules. Recently, human SIGIRR was found to act as a coreceptor with IL-18Ra for the recognition of IL-37, uncovering the existence of a previously unknown mechanism underlying the SIGIRR-mediated inflammatory regulation (3,53). Although well identified in mammals and predicted to be conserved from chicken to humans on the basis of sequence and expression patterns (54), the occurrence and existence of the SIGIRR homolog in lower vertebrates, including teleost fish, are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Toll/IL-1R (TIR)8 or IL-1R8, is an important member of the TLR/IL-1R superfamily (1)(2)(3)(4). In contrast with other TIR family members, SIGIRR comprises a single extracellular Ig domain, a transmembrane region, and a conserved intracellular TIR domain with substitutions of the two amino acid sites (Ser 447 and Arg-Tyr 536 ) required for the signaling of IL-1RI, as well as a unique 95-aa-long cytoplasmic tail, which differentiates SIGIRR from other TIR-containing family members (4,5).…”
Section: S Ingle Ig Il-1r-related Molecule (Sigirr) Also Known Asmentioning
confidence: 99%
“…Il-37 can bind to IL-18Ra, subsequently dimerizing with IL-1R8/ SIGIRR (as opposed to IL-18Rb that initiates IL-18 signaling); this IL-18Ra/IL-1R8 complex then recruits and inhibits the proinflammatory adaptor protein, MyD88, preventing the activation of downstream NF-jB-dependent events [12]. Alternatively, (and similar to IL-1a and IL-33), IL-37 may serve as an intracellular nuclear factor, directly binding to DNA elements and downregulating transcription of proinflammatory mediators.…”
Section: Concepts and Controversies Surrounding The Function Of Il-37mentioning
confidence: 99%